Benefits of WEB 2.0 Social Network Communication in Institutional PR - Velichkova, Svetozara (Research Papers, 2025)
The article is an attempt to trace the advantages of Web 2.0 communication through social networks for the needs of institutional PR, as well as to analyze the new activities that institutional PR practitioners must implement in the digital era.The aim is to present the online communication tools that are part of digital PR and their advantages over traditional PR tools.The conclusions are that the institutional PR practitioners in Bulgaria are already actively applying the new online communication tools, because of the advantages they provide, as the most actively used tool is Web 2.0 communication through social networks.There are institutions with better developed online communication, but there are also those where this process is yet to develop in the future. The scientific research methods used are general scientific methods – logical analysis and synthesis, induction, deduction and observation.The scientific research methods used are general scientific methods – logical analysis and synthesis, induction, deduction and observation.
Keywords: Institutional PR; Digital PR; Web 2.0 communication; Social networks